Success Case: Technical and Operational Assurance of Blasting Near Neighboring Mine Structures - Paulo C. Fernández A; Claudio C. Gajardo; Hector O. Romero (International Society of Explosives Engineers, 2025)
Phase 06 of the Los Bronces mine, currently under extraction for development, has the particularity of being close to the installations and buildings of a neighboring copper mine. Therefore, the blasts must ensure the continuity of the operation without affecting the nearby structures of the neighboring district, which include Maintenance sheds and Warehouse. Specifically, the safeguards consider a scenario that includes: - Flyrock projections (<150m) - Edge profile studies - Vibrations according to the NCh3577 standard - Nitrous gases Additionally, Phase 06 is also within Los Bronces, so strict control over spillage into the pit is necessary to avoid blocking ramp access to this level. The challenge lies in protecting not only the operation and facilities of the neighboring mining district but also the operability of Los Bronces. Thus, addressing these considerations, blasting configurations are developed with prior simulation of vibration models, flyrock, and spillage in all blasts, with strict control of technical design and implementation to ensure the results. Currently, blasts are successfully executed with control of projections based on the proximity of the projects, vibration (<40mm/s) with decoupling of holes of 17 mm/s between holes, reactive rock tests for explosive selection (loading advancement), and spillage simulation inside the pit according to the loading design; thus, ensuring operational continuity and mine development.